Characteristics of urban male homeless veterans and non-veterans in Omaha, Nebraska. Issue 1 (2nd January 2017) - Ramaswamy, Sriram; Driscoll, David; Tsai, Jack; Rose, Jodette; Smith, Lynette M.; Rosenheck, Robert A.
ABSTRACT: The current study examined differences between urban homeless veterans and non-veterans on sociodemographics, housing, clinical characteristics, and psychosocial factors. We recruited a sample of 196 homeless men (101 veterans, 95 non-veterans) from the Omaha, Nebraska metropolitan area. Structured interviews were conducted by research staff. The results showed that the two groups were similar in most respects, though there were several notable differences. Homeless veterans were found to be older and more educated than non-veterans, more likely to have married, and reported having fewer non-adult children. Multivariable models controlling for age further showed that veterans reported a higher number of medical problems and were more likely to report being diagnosed with major depression or PTSD than non-veterans. Comparison with previous studies suggests changes in certain characteristics of homeless veterans over the past few decades that may reflect the growing proportion of veterans from the all-volunteer force, initiated after the draft ended in 1975. Findings from this study were consistent with previous comparative studies suggesting limited changes in recent decades in the characteristics of homeless veterans as compared to non-veterans, although the high prevalence of major depression and PTSD merit special treatment for these disorders.